Radio Variability from a Quiescent Stellar-mass Black Hole Jet - Plotkin, Richard; Miller-Jones, James; Chomiuk, L.; Strader, J.; Bruzewski, S.; Bundas, A.; Smith, K.R.; Ruan, J.J. (IOP PUBLISHING LTD, 2019)
© 2019 The American Astronomical Society. All rights reserved. Relativistic outflows are believed to be a common feature of black hole X-ray binaries (BHXBs) at the lowest accretion rates, when they are in their "quiescent" spectral state. However, we still lack a detailed understanding of how quiescent jet emission varies with time. Here we present 24 yr of archival radio observations (from the Very Large Array and the Very Long Baseline Array) of the BHXB V404 Cygni in quiescence (totaling 150 observations from 1.4 to 22 GHz). The observed flux densities follow lognormal distributions with means and standard deviations of (logf v ,σ log f v ) = (-0.53, 0.19) and (-0.53, 0.30) at 4.9 and 8.4 GHz, respectively (where f v is the flux density in units of mJy). As expected, the average radio spectrum is flat with a mean and standard deviation of (α r σ αr ) (0.02, 0.65), where f v ∝ v αr . We find that radio flares that increase the flux density by factors of 2-4 over timescales as short as <10 minutes are commonplace, and that long-term variations (over 10-4000 day timescales) are consistent with shot-noise impulses that decay to stochastic variations on timescales ∼10 days (and perhaps as short as tens of minutes to several hr). We briefly compare the variability characteristics of V404 Cygni to jetted active galactic nuclei, and we conclude with recommendations on how to account for variability when placing quiescent BHXB candidates with radio luminosities comparable to V404 Cygni (LR ≈ 10 28 erg s -1 ) onto the radio/X-ray luminosity plane.